The seven principles of online learning: Feedback from faculty and alumni on its importance for teaching and learning - Cynthia Janet Tanis (Association for Learning Technology, 2020)
Effective online teaching and learning requires a carefully designed classroom that promotes student engagement with faculty, peers and course content. This research included an investigation of the importance of faculty-student communication and collaboration; student-student communication and collaboration; active learning techniques; prompt feedback; appropriate time for tasks; high performance expectations; and respect for diverse learning styles (preferences) (Chickering and Ehrmann 1996) to faculty in their online teaching and to alumni in their online learning. The participants were 14 college faculty and 111 alumni, from the same graduate program. A 45-item Likert survey and two open-ended questions were presented to the participants to explore the important factors contributing to their online teaching and learning. The results demonstrated that holding students to high standards of performance, academic honesty and professional conduct was the most important factor to both faculty in their online teaching and alumni in their online learning. Additionally, alumni valued engagement with their faculty more than engagement with other students or course content. Students need an online instructor who is organised and communicative in the online classroom, and faculty need a solidly designed online classroom, with engaged students who are timely in their work. An analysis of the findings with specific application to online teaching and learning is presented in this article.